Effectiveness Processing Rubbish into handicraft goods - Markonah, Markonah; Saripudin, Saripudin; Suryanto, Suryanto (Dinasti International Journal of Management Science, 2024)
Management rubbish become goods craft the hand that has it mark sell is very useful thing. Can reduce amount piled up rubbish, stuff processed Can made useful stuff for life man. Method used is a participatory method, with participation active from public in every stage research, start from planning, implementation, up to evaluation. Started from collection waste plastic, change rubbish especially plastic and can waste become items that have mark sell so that give impact to Society. with obtain the Goods Can used in life every day and also give income addition, if goods the traded